Media Literacy, Student Reading Engagement, and Text Genre Exposure: Determinants of Evaluative Reading Comprehension among Grade 9 Students - Calimutan, Irene Grace; Barcelona, Kriscentti Exzur (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the influence of media literacy, reading engagement, and text genre exposure on evaluative reading comprehension among Grade 9 learners, addressing the persistent gap in higher-order reading skills. Anchored on Rosenblatt’s transactional theory, Alagaran’s explore–engage–empower model, Fredricks et al.’s engagement theory, and Paré’s rhetorical genre theory, the research employed a descriptive-correlational design. Data were collected from 187 Grade 9 students in a public secondary school using a composite survey and a 50-item evaluative reading comprehension test adapted from validated instruments. Descriptive statistics and regression analysis were utilized to determine levels and relationships among variables. Findings revealed that learners demonstrated high levels of media literacy and reading engagement, moderate text genre exposure, and a very good level of evaluative reading comprehension, although variations in performance were observed. Among the variables examined, only media literacy significantly predicted evaluative reading comprehension, indicating its critical role in developing higher-order literacy skills. In contrast, reading engagement and text genre exposure were not significant independent predictors, suggesting that participation and exposure alone are insufficient without deeper critical processing. The results highlight the need for instructional approaches that integrate media literacy, promote sustained engagement, and diversify text exposure to strengthen evaluative reading skills. The study concludes that evaluative reading comprehension is shaped by the interaction of multiple literacy-related factors and recommends the integration of media literacy into classroom instruction, alongside the enhancement of critical thinking and analytical skills. This study supports SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions) by promoting critical literacy and informed decision-making. It contributes to educational and socio-digital sustainability by fostering learners’ ability to critically engage with information, navigate complex media environments, and participate responsibly in society.